Simulation and experimental study of motorcycle engine fueled with hho enriched gasoline - Vo, Anh Vu; Bui Van Ga; Le Khac Binh; Pham Van Quang (Vietnam Journal of Science and Technology, 2025)
The study presents the results of simulation and experimental research on the effects of HHO addition to gasoline motorcycle engine. The results show that adding HHO to gasoline improves combustion efficiency, resulting in increased maximum pressure. Compared to an engine fueled with neat gasoline, the brake power improvement is 3.8%, 7.1%, and 12.1% when substituting 5%, 7%, and 10% of gasoline with HHO, respectively. The increase in combustion temperature due to the addition HHO to gasoline results in higher NOx concentrations in the exhaust gas. Specifically, NOx concentrations increase by approximately 17%, 67%, and 140% when substituting 5%, 7%, and 10% of gasoline with HHO, respectively, compared to the gasoline fueling mode. Increasing the advanced ignition angle slightly decreases CO concentration but significantly increases NOx concentration. For engines running on gasoline supplemented with HHO, the optimal ignition advance angle is reduced by 5°CA compared to the neat gasoline fueling mode. Increasing engine speed decreases indicated engine work cycle and NOx concentration in exhaust gases while causing a slight increase in CO concentration. The discrepancy between the output power and CO concentration provided by the simulation and the experimental results is less than 10%.